Hervormde spore op die Tukkie kampus – "n Kroniek van die tweede 50 jaar - Ungerer, André G. (HTS teologiese studies, 2017)
This article is about the 2nd half (50 years) of the centenary of the Nederduitsch Hervormde Kerk van Afrika (NHKA) at the University of Pretoria (UP). The NHKA was the first church to join the Faculty of Theology at UP in 1917. The previous article ‘Hervormde footprints on the Tukkie campus – a chronicle of the first fifty years’ contains the humble beginnings, the steady growth, the political background during the apartheid years, and the NHKA’s role in justifying apartheid. The 70s and the 80s was a flourishing time for the Church with a steady growth in membership, an increase in the number of lecturers and students, and more or less enough money to sustain theology education at UP. During the nineties there was a decrease in membership numbers with the pivot point in 1992: from thereon there was a steady decline which was accelerated by the church schism in 2011 and onward. The two Sections of the NHKA and the Nederduitse Gereformeerde Kerk (NGK), Section A and B, became one in 2000. The Reformed Theology College (RTC), with the aim of church specific education for students of the NHKA, was also established in 2000 with prof. T.F.J. Dreyer as the first head. In November 2015 a student protest action #FeesMustFall rocked the foundation of higher education in South Africa. The issue of language and curriculum as aftermath of the protest actions was also at stake during 2016. During 2017 the centennial celebration of the Faculty of Theology at UP will take place. It coincides with REFO 500 – the commemoration of 500 years of the Reformation.